Takeaways from the special issue on The Practice of Replication - W. Robert Reed (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
In July 2017, Economics: The Open Access, Open Assessment E-Journal issued a call for papers for a special issue on 'The Practice of Replication.' In that call, the journal explained that there was no generally accepted procedure for how to do a replication. Likewise, there was no generally accepted standard for determining whether a replication 'confirms or disconfirms' an original study. Accordingly, the journal called for papers to identify principles for how to do a replication and how to interpret its results; and to apply those principles in crafting a replication plan for a study of the author's choosing. The hope was that this exercise would produce some progress on 'the practice of replication.' The special issue is now complete with a total of eight journal articles. This commentary places the respective articles within a common framework and identifies observations and lessons learned from the respective studies.
Keywords: C10; C18; C50; 330; replication; pre-analysis plan; reproduction; repetition; extension; robustness